A TiO2 nanotube composite copper-based silicon-based catalyst, preparation method and application thereof
The TiO2 nanotube composite copper-based silicon-based catalyst addresses the thermal stability and cost issues of existing copper-based catalysts by providing high surface area and stability, effectively dehydrogenating hydroxyl-containing organic compounds to produce lactones.
Patent Information
- Application Number
- CN201911044678.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-10-30
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2039-10-30
AI Technical Summary
Existing copper-based catalysts for dehydrogenating hydroxyl-containing organic compounds suffer from low thermal stability and high cost, limiting their industrial application, particularly in the production of valuable lactones like p-dioxanone.
A TiO2 nanotube composite copper-based silicon-based catalyst is developed, incorporating copper and silicon components supported on TiO2 nanotubes, with optional promoter elements, prepared through a method involving hydrothermal treatment and calcination, offering high surface area and thermal stability.
The catalyst exhibits improved thermal stability and high surface area, leading to enhanced performance in dehydrogenating hydroxyl-containing organic compounds to form lactones, with a simple and cost-effective preparation process.
Abstract
Description
Technical Field
[0001] The present invention relates to a TiO2 nanotube composite copper-based silicon-based catalyst. More specifically, the present invention relates to a TiO2 nanotube composite copper-based silicon-based catalyst and a preparation method. The present invention also relates to the use of the TiO2 nanotube composite copper-based silicon-based catalyst in the dehydrogenation of hydroxyl-containing organic compounds to form lactones. Background Art
[0002] Copper-based catalysts have a wide range of uses in industrial hydrogenation and dehydrogenation. They can be used for hydrogenation of carbon monoxide to methanol, hydrogenation of nitrobenzene to aniline, hydrogenation of octanal to octanol, hydrogenation of maleic anhydride to 1,4-butanediol, hydrogenation of oxalate to ethylene glycol, dehydrogenation of 1,4-butanediol to produce γ-butyrolactone, and dehydrogenation of diethylene glycol to produce p-dioxanone. Among these hydrogenation and dehydrogenation products, p-dioxanone is a very expensive monomer and is mainly used to produce poly(p-dioxanone). Similar to commercial polyesters such as polyglycolic acid (PGA), copolymers of glycolide and lactide, polylactic acid (PLA) and polycaprolactone (PCL), poly(p-dioxanone) (PPDO) has excellent biocompatibility, bioabsorbability and biodegradability. With the rapid development of green renewable energy and materials in recent years, it has attracted more attention from academia and industry. Polydioxanone (PPDO) was first successfully developed by Ethicon in the United States in the 1970s. After nearly 50 years of technological development, the current mainstream product is named PDS Ⅱ, which is approved by the U.S. Food and Drug Administration (FDA) as a medical absorbable surgical suture. It is suitable for suturing soft tissues, including pediatric cardiovascular tissues and ophthalmic surgeries, and is especially suitable for areas that require absorbable sutures and long-term wound support (up to six weeks).
[0003] p-Dioxanone was first reported in the 1930s and 1950s. US2142033, US2807629, and US2900395 used inert carriers to load reduced copper and chromium as active components. At a reaction temperature of 240-360°C, diethylene glycol was introduced into a fixed bed reactor for dehydrogenation and cyclization. Finally, high-purity p-dioxanone solid was obtained after separation and purification, and the yield was only 25%. Union Carbide Chemicals & Plastics Technology Corporation modified the copper-chromium catalyst in the US5675022 patent and used it for gas-phase oxidation of diethylene glycol to produce p-dioxanone, and then obtained p-dioxanone by melting. The copper-chromium catalyst was optimized in the US5310945 patent and the JP2000-351775 patent, but the activity of catalytic dehydrogenation of diethylene glycol has not reached a good level. The catalyst was deactivated due to carbon deposition and catalyst sintering after 140 hours and 100 hours of reaction. Based on the problems existing in the previous technology, South Korea's MEDICHEM CO LTD further modified the copper-chromium catalyst in the WO2009017261 patent, and obtained a mixed solution of p-dioxanone with high selectivity. Then, isopropanol and C6-C7 saturated hydrocarbons were used as recrystallization solvents, and p-dioxanone products were obtained in the presence of hydroxyl inhibitors and dehydrating agents. The product purity can reach 99.99%, the moisture content is less than 70ppm, and the total yield is 78%-80%. Patent ZL20051002120.3 discloses a catalyst for preparing p-dioxanone, which includes an inert carrier and an active component composed of a copper compound, a zinc compound and a catalytic promoter supported thereon, wherein the catalytic promoter is composed of an alkali metal or alkaline earth metal compound and a rare earth metal compound. The content of the active component is 20-90% based on the weight of the catalyst, wherein the content of the zinc compound is 0.3-3.0 in terms of the molar ratio to the copper compound, the content of the alkali metal or alkaline earth metal compound in the catalytic promoter is 0.01-0.2 in terms of the molar ratio to the copper compound, and the content of the rare earth metal compound in the catalytic promoter is 0.01-0.05 in terms of the molar ratio to the copper compound, and the catalyst is prepared by a co-precipitation method.
[0004] In the existing background technology, due to the low melting point and Tammann temperature of copper (1083℃ and 405℃ respectively), copper nanoparticles are very easy to sinter during high-temperature calcination, reduction and reaction. Yao Yuangen and others from the Institute of Research on the Structure of Matter, Fuzhou, Chinese Academy of Sciences, used the sol-gel method to introduce Cu-MOF precursors in the preparation of catalysts to regulate the size and dispersion of copper species in the final catalyst. The resulting Cu / SiO2-MOF catalyst used for dimethyl oxalate hydrogenation is twice the life of conventional copper-silicon catalysts (Synthesis of Robust MOF-Derived Cu / SiO2 Catalyst with Low Copper Loading via Sol–Gel Method for the Dimethyl Oxalate Hydrogenation Reaction, ACS Catalysis, 2018, Vol. 8, No. 4, pp. 3382-3394). Although this technology solves the problem of good copper dispersion at low copper content but low activity after encapsulation, and improves the activity and stability of low copper content catalysts, the cost of using MOFs as a matrix is high and industrialization is difficult.
[0005] In summary, the preparation of a nano copper catalyst with small particle size, high dispersion and good thermal stability is the key to the industrial implementation of dehydrogenation of hydroxyl-containing organic compounds to form lactones. Summary of the invention
[0006] The inventors have found through diligent research based on the prior art that by using TiO2 nanotubes as the original matrix and combining them with appropriate copper, silicon and auxiliary elements as needed, the prepared catalyst has good performance in dehydrogenating hydroxyl-containing organic compounds to form lactones, thereby completing the present invention.
[0007] In a first aspect, the present invention provides a TiO2 nanotube composite copper-based silicon-based catalyst, characterized in that the catalyst contains TiO2 nanotubes, a copper component and a silicon component supported on the TiO2.
[0008] In one embodiment, for the catalyst, a portion of greater than or equal to 50 wt % to 90 wt % of the copper component, calculated as CuO, is supported within the TiO 2 nanotubes.
[0009] In one embodiment, the catalyst further contains other oxygen components and promoter elements in addition to the TiO2, wherein the promoter elements are at least one metal selected from alkali metals, alkaline earth metals, transition elements, other Group IB metals other than Cu, Group IIB, Group IIIA, Group IVA and Group VA.
[0010] Preferably, the auxiliary element is at least one metal selected from the following: Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, Zr, Nb, W, Mn, Re, Fe, Ru, Co, Ni, Pd, Pt, Au, Zn, Cd, Al, Ga, In, Sn, Pb, Sb, Bi, La, Ce, Nd, V, Ag, Mo,
[0011] In one embodiment, for the catalyst, the content of the copper component (calculated as CuO) is 2 to 40 wt%, preferably 5 to 30 wt%, based on the total weight of the catalyst. In one embodiment, for the catalyst, the content of the silicon component (calculated as SiO2) is 1 to 18 wt%, preferably 2 to 15 wt%. In one embodiment, the catalyst contains the auxiliary agent, and the content of the auxiliary agent element (calculated as the oxide of the auxiliary agent) is 0 to 6.0 wt%, preferably 0 to 5.9 wt%, further preferably 0.001 to 5.0 wt%, more preferably 0.1 to 4.0 wt%,
[0012] In one embodiment, for the catalyst, the content of the TiO2 nanotubes is 48-97 wt %, preferably 50-92.9 wt %, and more preferably the remainder, based on the total weight of the catalyst.
[0013] In one embodiment, for the catalyst, wherein the catalyst is essentially composed of the TiO2 nanotubes, the copper component, the silicon component and the promoter element.
[0014] In one embodiment, for the catalyst, the TiO2 nanotube composite copper-based silicon-based catalyst has a BET specific surface area of 100 to 330 m 2 g -1 , preferably 110~230m 2 g -1 The most probable pore size is 9~16nm, and the pore volume is 0.4~1.2mlg -1 , preferably 1.0~2.1mlg -1 The specific surface area of copper measured by N2O titration is 23~80 m 2 g -1 .
[0015] The specific surface area of copper was determined by the method described by Antonella Gervasini et al. in "Dispersion and surface states of copper catalysts by temperature-programmed-reduction of oxidized surfaces (s-TPR)" in Applied Catalysis A: General, Vol. 281 (Issue 1-2), pp. 199-205, 2005, which includes: pre-reducing the copper catalyst, then oxidizing it with N2O, and then reducing it with H2 at a programmed temperature. The specific surface area of copper was calculated using MSA (m 2 g -1 Cu ) = MolH2SF.A / 10 4 C M W Cu calculate.
[0016] In a second aspect, the present invention further provides a method for preparing the catalyst described in the first aspect, comprising the following steps:
[0017] (1) adding TiO2 powder to 5-40wt% alkali solution, and subjecting to hydrothermal reaction at 100-180°C for 12-48 hours to obtain a hydrothermal product;
[0018] (2) filtering and washing the hydrothermal product, and then drying it to obtain a solid containing titanic acid;
[0019] (3) Primary contact step: contacting the solid containing titanic acid in step (2) with a precursor containing copper and an optional auxiliary metal element for 0.5-5 hours to obtain a primary contact product A;
[0020] (4) a second contacting step: contacting the primary contact product A of step (3) with a precursor containing silicon element for 0.5-5 hours to obtain a second contact product; and
[0021] (5) The second contact product is calcined in an air atmosphere containing an organic alcohol to obtain a TiO2 nanotube composite copper-based silicon-based catalyst.
[0022] In one embodiment, in step (1), the alkali solution is a NaOH aqueous solution or a KOH aqueous solution.
[0023] In one embodiment, in step (2), the drying temperature is 40-85° C., and the drying time is 0.5-10 hours.
[0024] In one embodiment, in step (3), the copper-containing precursor is preferably a soluble salt of copper, more preferably a water-soluble salt of copper, and further preferably at least one selected from the group consisting of copper nitrates, sulfates, sulfites, phosphates, halides, hydrogen phosphates, carbonates, bicarbonates, and ammonium salts.
[0025] In one embodiment, in step (3), the substance containing the auxiliary agent is preferably a soluble salt of the auxiliary agent, and more preferably at least one of the nitrate, sulfate, sulfite, phosphate, halide, hydrogen phosphate, carbonate, bicarbonate, and ammonium salt of the auxiliary agent.
[0026] In one embodiment, in step (3), in order to ensure that the solid of titanic acid is in full contact with the precursor containing copper and the precursor of the auxiliary agent, an organic solvent or water is selected as the solvent. The organic solvent is selected from at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol or tert-butanol.
[0027] According to the present invention, in the primary contact step of step (3), there is no particular restriction on the order of contacting the raw material components (i.e., the titanate-containing solid, the copper-containing precursor, and the auxiliary component precursor). Furthermore, according to the present invention, there is no particular restriction on the manner of carrying out the contact step, as long as the raw material components can be fully contacted and a uniform contact product can be formed. For example, the raw material components can be mixed (with auxiliary stirring if necessary) in any manner known in the art until they are uniform.
[0028] If necessary, in order to make the contact more uniform and sufficient, or to facilitate the contact, the contact step can also be carried out in the presence of a dispersion medium such as water. The contact product obtained at this time may be in the form of a slurry or paste.
[0029] In one embodiment, in step (3), the primary contact step can be carried out at any temperature from 0°C to 150°C, for example, at room temperature. When the temperature is higher than the boiling point of the dispersion medium, it can be carried out in a pressure vessel so that the boiling point corresponding to the pressure is higher than the temperature. From the perspective of convenience, room temperature is preferred, but it is not limited thereto as required. The contact time is based on obtaining a uniform primary contact product, generally 0.5 to 5 hours, and it is not limited thereto as required.
[0030] According to the present invention, after the preparation of the primary contact product in step (3), especially when the contact product is in a slurry state, it can be dried by any method known in the art as needed, such as oven drying (for example, at 60 to 150° C., preferably at 70 to 120° C.), air drying, or air drying, so as to remove any dispersion medium (for example, water) that may be introduced during its preparation, thereby obtaining a dry primary contact product for the calcination step.
[0031] According to the present invention, the contacting in step (3) may be carried out in the presence of additives such as a metal complexing agent (preferably a water-soluble metal complexing agent), a stabilizer, a pH adjuster, and the like.
[0032] In one embodiment, in step (4), the silicon-containing substance is selected from at least any one of methyl silicate, ethyl silicate, propyl silicate, butyl silicate, aminopropyltriethoxysilane, and sodium silicate.
[0033] According to the present invention, in the second contacting step of step (4), there is no particular restriction on the order of contacting the raw material components (i.e., the primary contact product or the optionally dried primary contact product of step (3), and the silicon component precursor). Furthermore, according to the present invention, there is no particular restriction on the manner of carrying out the contacting step, as long as the raw material components can be fully contacted and a uniform contact product can be formed. For example, the raw material components can be mixed (with auxiliary stirring if necessary) until they are uniform in any manner known in the art.
[0034] Optionally, in order to make the contact more uniform and sufficient, or to facilitate the contact, the second contact step can also be carried out in the presence of a dispersion medium such as water. The second contact product obtained at this time may be in the form of slurry or paste.
[0035] The second contacting step can be carried out at any temperature between 0°C and 150°C, for example, at room temperature. When the temperature is higher than the boiling point of the dispersion medium, it can be carried out in a pressure vessel so that the boiling point corresponding to the pressure is higher than the temperature. From the perspective of convenience, room temperature is preferred, but it is not limited thereto as required. The contacting time is based on obtaining a uniform contact product, generally 0.5 to 5 hours, but it is not limited thereto as required.
[0036] According to the present invention, after the second contact product is prepared, especially when the contact product is in a slurry state, it can be dried by any method known in the art as needed, such as oven drying (e.g., at 60-150° C., preferably at 70-120° C.), air drying, or air drying, so as to remove any dispersion medium (e.g., water) that may be introduced during its preparation. According to the present invention, the dried contact product is also simply referred to as a contact product.
[0037] According to the present invention, the second contacting step may be performed in the presence of additives such as a metal complexing agent (preferably a water-soluble metal complexing agent), a stabilizer, a pH adjuster, and the like.
[0038] In one embodiment, the primary contact and the secondary contact in the preparation method of the present invention may each be performed in the presence of a metal complexing agent, and the weight ratio of the metal complexing agent to the copper component precursor is 0.4 to 2.0.
[0039] As the metal complexing agent, for example, polycarboxylic acids, monohydric alcohols, polyols and polyamines can be cited. These metal complexing agents can be used alone or in combination as needed. When used in combination, the weight ratio of the total amount of each metal complexing agent to the vanadium component precursor meets the above requirements, that is, 0.4 to 2.0.
[0040] Examples of the polycarboxylic acid include C 2-20 Alkanes include oxalic acid, succinic acid, adipic acid, etc. As the polycarboxylic acid, C 2-10 (preferably 3-6) carboxyl groups and one or more hydroxyl groups (for example, 1-6) may be mentioned. 2-20 Alkanes include malic acid, tartaric acid, citric acid, etc. Alternatively, the polycarboxylic acid may be 2-20 Examples of polycarboxyalkyl (poly)amines obtained by inserting one or more nitrogen atoms into an alkane chain include nitrilotriacetic acid and ethylenediaminetetraacetic acid.
[0041] Examples of the monohydric alcohol include C 1-20 Examples of the alkane include methanol, ethanol, n-propanol, isopropanol, n-butanol and isobutanol.
[0042] Examples of the polyol include C 2-20 Alkanes, such as ethylene glycol, or polymers of the polyols, such as polyethylene glycol, etc., or can also be in the C 2-20 Polyhydroxyalkyl (poly)amines obtained by inserting one or more nitrogen atoms into an alkane chain include, for example, monoethanolamine and triethanolamine.
[0043] Examples of the polyamine include ethylenediamine, diethylenetriamine, triethylenetetramine, and the like.
[0044] As the stabilizer, those known in the art can be used, for example, ammonium chloride and ammonium sulfate, etc. As the pH adjuster, for example, hydrochloric acid, ammonia water, etc. can be mentioned.
[0045] In one embodiment, in step (5), the organic alcohol is selected from at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol or tert-butanol.
[0046] In one embodiment, in step (5), the weight ratio of the amount of entrained organic alcohol to air is 1:100-1:800.
[0047] In one embodiment, in step (5), the calcination temperature is 200-450°C.
[0048] The present invention also provides application of the catalyst in dehydrogenating hydroxyl-containing organic compounds to form lactones.
[0049] The hydroxyl-containing organic compound that can be used in the present invention refers to a compound with hydroxyl groups on two or more carbon atoms in the carbon backbone. The organic compound includes a compound composed of a carbon backbone, oxygen, and hydrogen, and also includes a compound in which the carbon atoms in the carbon chain are substituted by other heteroatoms such as sulfur and nitrogen. Preferably, it is a compound with hydroxyl groups on two carbon atoms, and more preferably 1,4-butanediol and diethylene glycol.
[0050] According to the application of the present invention, the catalyst of the present invention is brought into contact with a hydroxyl-containing organic compound, and the hydroxyl compound is dehydrogenated into a ring to form a lactone through a catalytic dehydrogenation reaction.
[0051] In addition to the reaction conditions specified below, the contact reaction can be carried out in any manner known in the art (such as contact method, reaction vessel, catalyst feeding method, or hydroxyl-containing organic compound raw material feeding method, etc.).
[0052] According to the present invention, the conditions for the catalytic dehydrogenation reaction include: a reaction temperature of 200-300°C, preferably 230-300°C, a pressure of normal pressure to 2 MPa, preferably normal pressure to 0.2 MPa, and a space velocity of 0.1-1.2 h -1 , preferably 0.1~0.8h -1 The reaction atmosphere is at least one of hydrogen, nitrogen, helium, argon and carbon dioxide, and the gas space velocity is 1000-5000h -1 .
[0053] If necessary, the hydroxyl-containing organic compound may be preheated to 80-260° C., preferably 100-250° C., before contacting with the catalyst.
[0054] Beneficial Effects
[0055] Compared with the prior art (ACS Catalysis, 2018, Vol. 8, No. 4, pp. 3382-3394), the catalyst preparation method provided by the present invention is simple and feasible, and has the technical characteristics of low cost, no heavy metal chromium, and environmentally friendly. Compared with the existing catalyst for dehydrogenating hydroxyl compounds to lactones, the copper and auxiliary elements in the catalyst provided by the present invention are confined between TiO2 nanotubes and SiO2, and have the advantages of high surface area, grains that are not easy to grow during the reaction, and long life. Example
[0056] The present invention is further described in detail below using examples, but the present invention is not limited to these examples.
[0057] Example 1
[0058] 100 parts by weight of TiO2 powder was added to 500 parts by weight of 10% NaOH aqueous solution, and hydrothermally reacted at 120°C for 24 hours to obtain a hydrothermal product. The product after the hydrothermal reaction was filtered, washed, and dried at 60°C for 5 hours to obtain a solid containing titanic acid. 100 parts by weight of the dried solid was mixed with 30 parts by weight of copper nitrate, 5 parts by weight of manganese nitrate, and 3 parts by weight of oxalic acid aqueous solution, stirred, and dried at 80°C for 2 hours to obtain a dry product 1-1. The dry product 1-1 was mixed with 9 parts by weight of ethyl orthosilicate ethanol solution, and dried at 50°C for 6 hours to obtain a dry product 1-2. The TiO2 nanotube composite copper-based silicon-based catalyst A was calcined at 400°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst was measured to be 141 m 2 g -1 , its copper surface area is 32m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 12.9%, the weight percentage of Si (calculated as SiO2) was 2.2%, the weight percentage of Mn (calculated as MnO2) was 2.4%, and the weight percentage of Na (calculated as Na2O) was 0.3%.
[0059] Comparative Example 1
[0060] 100 parts by weight of TiO2 powder was added to 500 parts by weight of 10% NaOH aqueous solution, and hydrothermally reacted at 120°C for 24 hours to obtain a hydrothermal product. The product after the hydrothermal reaction was filtered, washed, and dried at 60°C for 5 hours to obtain a solid containing titanic acid. 100 parts by weight of the dried solid was mixed with 30 parts by weight of copper nitrate, 5 parts by weight of manganese nitrate, and 3 parts by weight of oxalic acid aqueous solution, stirred, and dried at 80°C for 2 hours to obtain a dry product 1-1. The dry product 1-1 was calcined at 400°C in a mixed atmosphere of air and n-propanol to obtain a TiO2 nanotube composite copper-based catalyst AC. The surface area of the catalyst was measured to be 162 m2 g -1 , its copper surface area is 27m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 13.2%, the weight percentage of Mn (calculated as MnO2) was 2.5%, and the weight percentage of Na (calculated as Na2O) was 0.3%.
[0061] Example 2
[0062] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% KOH aqueous solution, and perform hydrothermal reaction at 130°C for 48 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 70°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid, mix it with 40 parts by weight of copper nitrate, 8 parts by weight of sodium nitrate, and 12 parts by weight of oxalic acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 2-1. The dry product 2-1 is mixed with 15 parts by weight of ethyl orthosilicate ethanol solution, and dried at 50°C for 6 hours to obtain a dry product 2-2. The TiO2 nanotube composite copper-based silicon-based catalyst B is calcined at 400°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 134 m 2 g -1 , its copper surface area is 31m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 16.1%, the weight percentage of Si (calculated as SiO2) was 4.0%, and the weight percentage of Na (calculated as Na2O) was 2.3%.
[0063] Example 3
[0064] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% KOH aqueous solution, and perform hydrothermal reaction at 110°C for 48 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 65°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid, mix it with 40 parts by weight of copper nitrate, 8 parts by weight of potassium nitrate, and 20 parts by weight of citric acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 3-1. The dry product 3-1 is mixed with 10 parts by weight of ethyl orthosilicate ethanol solution, and dried at 50°C for 6 hours to obtain a dry product 3-2. The TiO2 nanotube composite copper-based silicon-based catalyst C is calcined at 400°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 150m 2 g -1 , its copper surface area is 39m 2 g -1The weight percentage of Cu (calculated as CuO) was measured to be 16.1%, the weight percentage of Si (calculated as SiO2) was 2.6%, and the weight percentage of K (calculated as K2O) was 3.4%.
[0065] Example 4
[0066] Take 100 parts by weight of TiO2 powder and add 500 parts by weight of 5% NaOH aqueous solution, and perform hydrothermal reaction at 150°C for 20 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 60°C for 8 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid, mix it with 45 parts by weight of copper nitrate, 8 parts by weight of magnesium nitrate, and 20 parts by weight of citric acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 4-1. The dry product 4-1 is mixed with 21 parts by weight of ethyl orthosilicate ethanol solution, and dried at 50°C for 6 hours to obtain a dry product 4-2. The TiO2 nanotube composite copper-based silicon-based catalyst D is calcined at 400°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 111m 2 g -1 , its copper surface area is 41m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 17.1%, the weight percentage of Si (calculated as SiO2) was 5.2%, and the weight percentage of Mg (calculated as MgO) was 2.0%.
[0067] Example 5
[0068] Take 100 parts by weight of TiO2 powder and add 300 parts by weight of 40% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 80°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid, mix it with 33 parts by weight of copper nitrate, 3 parts by weight of barium nitrate, and 20 parts by weight of citric acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 5-1. The dry product 5-1 is mixed with 21 parts by weight of ethyl orthosilicate ethanol solution, and dried at 50°C for 6 hours to obtain a dry product 5-2. The TiO2 nanotube composite copper-based silicon-based catalyst E is calcined at 400°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 129 m 2 g -1 , its copper surface area is 34m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 13.6%, the weight percentage of Si (calculated as SiO2) was 5.8%, and the weight percentage of Ba (calculated as BaO) was 1.7%.
[0069] Example 6
[0070] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid, mix it with 33 parts by weight of copper nitrate, 4 parts by weight of zirconium nitrate, and 20 parts by weight of citric acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 6-1. The dry product 6-1 is mixed with 21 parts by weight of ethyl orthosilicate ethanol solution, and dried at 50°C for 6 hours to obtain a dry product 6-2. The TiO2 nanotube composite copper-based silicon-based catalyst F is calcined at 400°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 118 m 2 g -1 , its copper surface area is 39m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 13.0%, the weight percentage of Si (calculated as SiO2) was 5.6%, and the weight percentage of Zr (calculated as ZrO2) was 1.4%.
[0071] Example 7
[0072] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid, mix it with 33 parts by weight of copper nitrate, 4 parts by weight of ammonium metatungstate, and 20 parts by weight of citric acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 7-1. The dry product 7-1 is mixed with 21 parts by weight of ethyl orthosilicate ethanol solution, and dried at 50°C for 6 hours to obtain a dry product 7-2. The TiO2 nanotube composite copper-based silicon-based catalyst G is calcined at 400°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 111m 2 g -1 , its copper surface area is 32m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 13.0%, the weight percentage of Si (calculated as SiO2) was 5.6%, and the weight percentage of W (calculated as WO3) was 3.5%.
[0073] Example 8
[0074] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid, mix it with 30 parts by weight of copper nitrate, 4 parts by weight of rhenium nitrate, and 20 parts by weight of citric acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 8-1. The dry product 8-1 is mixed with 16 parts by weight of ethyl orthosilicate ethanol solution, and dried at 50°C for 6 hours to obtain a dry product 8-2. The TiO2 nanotube composite copper-based silicon-based catalyst H is calcined at 400°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 145m 2 g -1 , its copper surface area is 41m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 12.6%, the weight percentage of Si (calculated as SiO2) was 4.5%, and the weight percentage of Re (calculated as Re2O3) was 2.3%.
[0075] Example 9
[0076] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 20 parts by weight of copper nitrate and 8 parts by weight of an aqueous solution of ferric nitrate, stir, and dry at 80°C for 2 hours to obtain a dry product 9-1. The dry product 9-1 is mixed with 16 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 9-2. The TiO2 nanotube composite copper-based silicon-based catalyst I is calcined at 400°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 123 m 2 g -1 , its copper surface area is 45m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 8.9%, the weight percentage of Si (calculated as SiO2) was 4.3%, and the weight percentage of Fe (calculated as Fe2O3) was 2.8%.
[0077] Example 10
[0078] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 30 parts by weight of copper nitrate and 5 parts by weight of ruthenium chloride aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 10-1. The dry product 10-1 is mixed with 16 parts by weight of tetraethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 10-2. The TiO2 nanotube composite copper-based silicon-based catalyst J is calcined at 400°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 114m 2 g -1 , its copper surface area is 37m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 12.7%, the weight percentage of Si (calculated as SiO2) was 4.3%, and the weight percentage of Ru (calculated as Ru2O3) was 2.8%.
[0079] Embodiment 11
[0080] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 40 parts by weight of copper nitrate and 8 parts by weight of nickel nitrate aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 11-1. The dry product 11-1 is mixed with 16 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 11-2. The TiO2 nanotube composite copper-based silicon-based catalyst K is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 114 m 2 g -1 , its copper surface area is 33m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 16.1%, the weight percentage of Si (calculated as SiO2) was 4.0%, and the weight percentage of Ni (calculated as NiO) was 3.1%.
[0081] Example 12
[0082] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 30 parts by weight of copper nitrate and 3 parts by weight of palladium chloride hydrochloric acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 12-1. The dry product 12-1 is mixed with 18 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 12-2. The TiO2 nanotube composite copper-based silicon-based catalyst L is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 127 m 2 g -1 , its copper surface area is 43m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 12.6%, the weight percentage of Si (calculated as SiO2) was 4.9%, and the weight percentage of Pd (calculated as PdO) was 2.1%.
[0083] Example 13
[0084] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 30 parts by weight of copper nitrate and 3 parts by weight of gallium chloride hydrochloric acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 13-1. The dry product 13-1 is mixed with 18 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 13-2. The TiO2 nanotube composite copper-based silicon-based catalyst M is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 133 m 2 g -1 , its copper surface area is 42m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 12.6%, the weight percentage of Si (calculated as SiO2) was 5.0%, and the weight percentage of Ga (calculated as Ga2O3) was 1.7%.
[0085] Embodiment 14
[0086] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 30 parts by weight of copper nitrate and 3 parts by weight of stannous chloride hydrochloric acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 14-1. The dry product 14-1 is mixed with 18 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 14-2. The TiO2 nanotube composite copper-based silicon-based catalyst N is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 141m 2 g -1 , its copper surface area is 40m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 12.6%, the weight percentage of Si (calculated as SiO2) was 5.0%, and the weight percentage of Sn (calculated as SnO2) was 2.3%.
[0087] Embodiment 15
[0088] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 30 parts by weight of copper nitrate and 3 parts by weight of stannous chloride hydrochloric acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 15-1. The dry product 15-1 is mixed with 18 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 15-2. The TiO2 nanotube composite copper-based silicon-based catalyst O is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 149 m 2 g -1 , its copper surface area is 41m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 12.6%, the weight percentage of Si (calculated as SiO2) was 5.0%, and the weight percentage of Sb (calculated as Sb2O3) was 1.9%.
[0089] Example 16
[0090] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 30 parts by weight of copper nitrate and 5 parts by weight of bismuth nitrate in nitric acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 16-1. The dry product 16-1 is mixed with 18 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 16-2. The TiO2 nanotube composite copper-based silicon-based catalyst P is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 141m 2 g -1 , its copper surface area is 43m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 12.3%, the weight percentage of Si (calculated as SiO2) was 5.0%, and the weight percentage of Bi (calculated as Bi2O3) was 2.8%.
[0091] Embodiment 17
[0092] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 30 parts by weight of copper nitrate and 5 parts by weight of lanthanum nitrate in oxalic acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 17-1. The dry product 17-1 is mixed with 18 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 17-2. The TiO2 nanotube composite copper-based silicon-based catalyst Q is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 141 m 2 g -1 , its copper surface area is 40m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 12.6%, the weight percentage of Si (calculated as SiO2) was 5.0%, and the weight percentage of La (calculated as La2O3) was 2.4%.
[0093] Embodiment 18
[0094] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 40 parts by weight of copper nitrate and 4 parts by weight of ammonium metavanadate in oxalic acid aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 18-1. The dry product 18-1 is mixed with 15 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 18-2. The TiO2 nanotube composite copper-based silicon-based catalyst R is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 111m 2 g -1 , its copper surface area is 27m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 16.1%, the weight percentage of Si (calculated as SiO2) was 3.8%, and the weight percentage of V (calculated as V2O5) was 2.8%.
[0095] Embodiment 19
[0096] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 45 parts by weight of copper nitrate and 4 parts by weight of silver nitrate aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 19-1. The dry product 19-1 is mixed with 19 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 19-2. The TiO2 nanotube composite copper-based silicon-based catalyst S is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 118 m 2 g -1 , its copper surface area is 26m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 17.7%, the weight percentage of Si (calculated as SiO2) was 4.7%, and the weight percentage of Ag (calculated as Ag2O) was 2.5%.
[0097] Embodiment 20
[0098] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 45 parts by weight of copper nitrate and 50 parts by weight of a hot aqueous solution of ammonium molybdate, stir, and dry at 80°C for 2 hours to obtain a dry product 20-1. The dry product 20-1 is mixed with 30 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 20-2. The TiO2 nanotube composite copper-based silicon-based catalyst T is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 121m 2 g -1 , its copper surface area is 26m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 17.3%, the weight percentage of Si (calculated as SiO2) was 7.1%, and the weight percentage of Mo (calculated as MoO3) was 0.7%.
[0099] Embodiment 21
[0100] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 40 parts by weight of copper nitrate and 8 parts by weight of cerium nitrate aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 21-1. The dry product 21-1 is mixed with 18 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 21-2. The TiO2 nanotube composite copper-based silicon-based catalyst U is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 161m 2 g -1 , its copper surface area is 37m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 15.8%, the weight percentage of Si (calculated as SiO2) was 4.6%, and the weight percentage of Ce (calculated as CeO2) was 3.9%.
[0101] Embodiment 22
[0102] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 30 parts by weight of copper nitrate, 3 parts by weight of sodium nitrate and 3 parts by weight of manganese nitrate aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 22-1. The dry product 22-1 is mixed with 18 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 22-2. The TiO2 nanotube composite copper-based silicon-based catalyst V is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 159 m 2 g -1 , its copper surface area is 44m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 12.6%, the weight percentage of Si (calculated as SiO2) was 4.7%, the weight percentage of Na (calculated as Na2O) was 1.1%, and the weight percentage of Mn (calculated as MnO2) was 1.5%.
[0103] Embodiment 23
[0104] Take 100 parts by weight of TiO2 powder and add 400 parts by weight of 20% NaOH aqueous solution, and perform hydrothermal reaction at 140°C for 30 hours to obtain a hydrothermal product. The product after the hydrothermal reaction is filtered, washed, and dried at 75°C for 5 hours to obtain a solid containing titanic acid. Take 100 parts by weight of the dried solid and mix it with 30 parts by weight of copper nitrate, 3 parts by weight of sodium nitrate, 3 parts by weight of manganese nitrate, and 3 parts by weight of bismuth nitrate aqueous solution, stir, and dry at 80°C for 2 hours to obtain a dry product 23-1. The dry product 23-1 is mixed with 18 parts by weight of ethyl orthosilicate propanol solution, and dried at 50°C for 6 hours to obtain a dry product 23-2. The TiO2 nanotube composite copper-based silicon-based catalyst W is calcined at 380°C in a mixed atmosphere of air and n-propanol. The surface area of the catalyst is measured to be 131 m 2 g -1 , its copper surface area is 43m 2 g -1 The weight percentage of Cu (calculated as CuO) was measured to be 12.1%, the weight percentage of Si (calculated as SiO2) was 4.8%, the weight percentage of Na (calculated as Na2O) was 1.0%, the weight percentage of Mn (calculated as MnO2) was 1.4%, and the weight percentage of Bi (calculated as Bi2O3) was 1.7%.
[0105] Comparative Example:
[0106] The catalyst prepared according to Example 6 of Sichuan University ZL20051002120.3, that is, 249.7 grams of copper sulfate pentahydrate (1 mol), 86.3 grams of zinc sulfate heptahydrate (0.3 mol), 7.4 grams of calcium chloride dihydrate (0.05 mol) and 14.2 grams of cerium chloride hexahydrate (0.04 mol) were mixed, 2500 mL of deionized water was added to dissolve, and then 1100 grams of aluminum oxide and 330 grams of silicon dioxide were added. Ammonium carbonate was added dropwise to pH = 7.0 at 35°C and under strong stirring. After precipitation, it was aged at 50°C for 50 minutes, and then filtered and washed to remove soluble metal compounds. The washed precipitate was dried at 120°C for 12 hours, and then calcined at 700°C for 3 hours. After the calcined particles were mixed evenly with starch, they were pressed into a cylindrical catalyst X of Φ5×5.
[0107] Embodiment 24
[0108] Diethylene glycol dehydrogenation catalytic performance test:
[0109] (1) The catalysts in Examples 1-23 and Comparative Examples 1-2 were respectively loaded into a fixed bed reactor and reduced under hydrogen conditions at 250°C for 2 hours, and then heated for 0.5 hours. -1 Diethylene glycol is pumped in at a weight space velocity of 1500 h / min and hydrogen at a volume space velocity of 1500 h / min. -1 , the reaction pressure was normal pressure, the reaction temperature was 270°C, and the results are shown in Table 1.
[0110] Table 1 Results of dehydrogenation of diethylene glycol to p-dioxanone over different catalysts
[0111] .
[0112] Although the present invention is described in detail herein with reference to exemplary embodiments, it should be understood that the present invention is not limited to the embodiments. Personnel with ordinary skills in the art and access to the teachings herein will recognize other variations, modifications and embodiments within the scope of the present invention. Therefore, the present invention should be broadly interpreted in accordance with the claims described below.
Claims
1. A TiO2 nanotube composite copper-based silicon-based catalyst, characterized in that: The catalyst contains TiO2 nanotubes, a copper component and a silicon component supported on the TiO2, wherein the content of the copper component is 8.9 to 30% by weight in terms of CuO based on the total weight of the catalyst, and is prepared by the following method, which comprises the following steps: (1) adding TiO2 powder to 5-40wt% alkali solution, and performing hydrothermal reaction at 100-180°C for 12-48 hours to obtain a hydrothermal product; (2) filtering and washing the hydrothermal product, and then drying it to obtain a solid containing titanic acid; (3) Primary contact step: contacting the solid containing titanic acid in step (2) with a precursor containing copper and an optional auxiliary metal element for 0.5-5 hours to obtain a primary contact product A; (4) a second contacting step: contacting the primary contact product A of step (3) with a precursor containing silicon element for 0.5-5 hours to obtain a second contact product; and (5) calcining the second contact product in an air atmosphere containing an organic alcohol to obtain the catalyst.
2. The catalyst according to claim 1, characterized in that Calculated as CuO, greater than or equal to 50 wt % to 90 wt % of the copper component is loaded in the TiO 2 nanotubes.
3. The catalyst according to claim 1, characterized in that Based on the total weight of the catalyst, the content of the silicon component is 1 to 18 wt% in terms of SiO2; and / or the content of the TiO2 nanotubes is 48 to 97 wt%, provided that the sum of the contents of all components of the catalyst is 100%.
4. The catalyst according to claim 1, characterized in that The catalyst also contains other oxygen components and auxiliary elements besides the TiO2. The auxiliary element is at least one metal selected from alkali metals, alkaline earth metals, transition elements, other IB group metals other than Cu, IIB group, IIIA group, IVA group and VA group.
5. The catalyst according to claim 4, characterized in that The auxiliary element is at least one metal selected from Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, Zr, Nb, Mn, Re, Fe, Ru, Co, Ni, Pd, Pt, Au, Zn, Cd, Al, Ga, In, Sn, Pb, Sb, Bi, La and Ce.
6. The catalyst according to claim 4, characterized in that Based on the total weight of the catalyst, the content of the silicon component is 1 to 18 weight % in terms of SiO2; and / or the content of the auxiliary element is 0.001 to 5.0 weight % in terms of the oxide of the auxiliary; and / or the content of the TiO2 nanotubes is 48 to 97 weight %; provided that the sum of the contents of all components of the catalyst is 100%.
7. The catalyst according to claim 6, wherein The catalyst is essentially composed of the TiO2 nanotubes, the copper component, the silicon component and the promoter element.
8. The catalyst according to claim 1, wherein The BET specific surface area of the catalyst is 100 to 330 m 2 g -1 ; and / or the most probable pore size is 9 to 16 nm, and the pore volume is 0.4 to 1.2 mlg -1 ; and / or the copper specific surface area measured by N2O titration is 23 to 80 m 2 g -1 .
9. The catalyst according to claim 1, wherein Based on the total weight of the catalyst, the content of the silicon component is 2 to 15% by weight as SiO2; and / or the content of the TiO2 nanotubes is 50 to 92.9% by weight, provided that the sum of the contents of all components of the catalyst is 100%; 10. The catalyst according to claim 4, wherein Based on the total weight of the catalyst, the content of the silicon component is 2 to 15 weight % in terms of SiO2; and / or the content of the auxiliary element is 0.1 to 4.0 weight % in terms of the oxide of the auxiliary; and / or the content of the TiO2 nanotubes is 50 to 92.9 weight %; provided that the sum of the contents of all components of the catalyst is 100%.
11. A method for preparing a catalyst as claimed in any one of claims 1 to 10, comprising the following steps: (1) adding TiO2 powder to 5-40wt% alkali solution, and performing hydrothermal reaction at 100-180°C for 12-48 hours to obtain a hydrothermal product; (2) filtering and washing the hydrothermal product, and then drying it to obtain a solid containing titanic acid; (3) Primary contact step: contacting the solid containing titanic acid in step (2) with a precursor containing copper and an optional auxiliary metal element for 0.5-5 hours to obtain a primary contact product A; (4) a second contacting step: contacting the primary contact product A of step (3) with a precursor containing silicon element for 0.5-5 hours to obtain a second contact product; and (5) calcining the second contact product in an air atmosphere containing an organic alcohol to obtain the catalyst.
12. The preparation method according to claim 11, wherein: In step (1), the alkali solution is a NaOH aqueous solution or a KOH aqueous solution; and / or In step (2), the drying temperature is 40-85° C. and the drying time is 0.5-10 hours; and / or In step (5), the organic alcohol is selected from at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol or tert-butanol; and / or In step (5), the weight ratio of the amount of the entrained organic alcohol to air is 1:100-1:800; and / or In step (5), the calcination temperature is 200-450°C.
13. Use of the catalyst according to any one of claims 1 to 10 in the dehydrogenation reaction of a hydroxyl-containing organic compound, wherein the hydroxyl group of the compound is dehydrogenated to form a lactone.
14. A method for dehydrogenating a hydroxyl-containing organic substance using the catalyst according to any one of claims 1 to 10, wherein the conditions for the catalytic dehydrogenation reaction include: The reaction temperature is 200-300°C; and / or The pressure ranges from normal pressure to 2MPa; and / or The space velocity of hydroxyl compounds is 0.1~1.2h -1 ; and / or The reaction atmosphere is at least one of hydrogen, nitrogen, helium, argon and carbon dioxide; and / or Gas space velocity is 1000-5000h -1 .
15. A method for dehydrogenating a hydroxyl-containing organic substance using the catalyst according to any one of claims 1 to 10, wherein the conditions for the catalytic dehydrogenation reaction include: The reaction temperature is 230-300°C; and / or The pressure is normal pressure to 0.2 MPa; and / or The space velocity of hydroxyl compounds is 0.1~0.8h -1 .
Citation Information
Patent Citations
Production of 2-p-dioxanone
JP2000351775A
Process for preparing para-dioxanones
US5310945A
Recovery of dioxanone by melt crystallization
US5675022A
Method for manufacturing ultrafine p dioxanone
WO2009017261A1
Catalyst for preparing cyclohexanone from cyclohexanol through gas-phase dehydrogenization and preparation method thereof
CN104511277A
